2021
DOI: 10.3389/fmed.2021.670337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean and Centroid of Surgically Induced Astigmatism After Standard Cataract Surgery

Abstract: Purpose: To compare the arithmetic mean of surgically induced astigmatism (M-SIA) and the centroid of surgically induced astigmatism (C-SIA) after standard cataract surgery.Methods: We retrospectively examined 200 eyes of 100 consecutive patients undergoing bilateral cataract surgery through a 2.8 mm temporal clear corneal incision. We quantitatively measured the magnitude and axis of corneal astigmatism preoperatively and 3 months postoperatively using an automated keratometer (TONOREFF-II, Nidek). We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
2
16
0
2
Order By: Relevance
“…In the current study, our findings demonstrate that the C-SIA was much smaller than the M-SIA in post-trabeculectomy patients, possibly because individual SIA showed variations in astigmatism in magnitude and direction in these patients. Both SIA findings of trabeculectomy were in good agreement with our previous SIA findings of cataract surgery and phakic intraocular lens implantation [ 13 , 14 ]. Therefore, we believe that the C-SIA is theoretically beneficial to understand the overall trend of SIA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, our findings demonstrate that the C-SIA was much smaller than the M-SIA in post-trabeculectomy patients, possibly because individual SIA showed variations in astigmatism in magnitude and direction in these patients. Both SIA findings of trabeculectomy were in good agreement with our previous SIA findings of cataract surgery and phakic intraocular lens implantation [ 13 , 14 ]. Therefore, we believe that the C-SIA is theoretically beneficial to understand the overall trend of SIA.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first study to unilaterally demonstrate the magnitude and the direction of SIA in a large cohort of patients undergoing trabeculectomy. It has been reported that standard cataract surgery through a 3 mm corneal incision caused a M-SIA of approximately 0.5 D [ 8 , 9 , 10 , 11 , 12 , 13 ]. We previously revealed that the C-SIA of cataract surgery and phakic intraocular lens implantation was far smaller than that of the M-SIA [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summated vector mean of SIA (SVM-SIA) consists of the magnitude and the meridian of corneal astigmatism. Hence, the SVM-SIA is considered clinically more meaningful in understanding general SIA tendencies [ 10 , 11 ] and might differ from the M-SIA [ 12 ]. Moreover, ICL surgery through a superior corneal incision may be beneficial for reducing astigmatism, especially when using a non-toric ICL in WTR astigmatic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…This method tends to over-estimate the change that occurs due to the test-to-test variability of corneal power and axis measurement. 24 An alternative is to derive the flattening that occurs on average on the incised meridian by vector analysis. 25 Once again that value depends on possibly inaccurate corneal measurement.…”
Section: Surgically Induced Astigmatismmentioning
confidence: 99%